French current management and oncological results of locally recurrent rectal cancer. Issue 12 (December 2015) - Denost, Q.; Faucheron, J.L.; Lefevre, J.H.; Panis, Y.; Cotte, E.; Rouanet, P.; Jafari, M.; Capdepont, M.; Rullier, E.; ,
Abstract: Background: There is a significant worldwide variation in practice regarding the criteria for operative intervention and overall management in patients with locally recurrent rectal cancer (LRRC). A survival benefit has been described for patients with clear resection margins in patients undergoing surgery for LRRC which is seen as an important surgical quality indicator. Methods: A prospective French national database was established in 2008 which recorded procedures undertaken for locally recurrent rectal cancer (LRRC). Overall and Disease-Free Survival (OS, DFS) were assessed retrospectively. We report the variability and the heterogeneity of LRRC management in France as well as 5-year oncological outcomes. Results: In this national report, 104 questionnaires were completed at 29 French surgical centres with a high variability of cases-loaded. Patients had preoperative treatment in 86% of cases. Surgical procedures included APER (36%), LAR (25%), Hartmann's procedure (21%) and pelvic exenterations (15.5%). Four patients had a low sacrectomy (S4/S5). There were no postoperative deaths and overall morbidity was 41%. R0 was achieved in 60%, R1 and R2 in 29% and 11%, respectively. R0 resection resulted in a 5-year OS of 35% compared to 12% and 0% for respectively R1 and R2 (OR = 2.04; 95% CI: 1.4–2.98; p < 0.001). OS was similar between R2 and non-resected patients (OR = 1.47; 95% CI: 0.58–3.76; p = 0.418). Conclusions: Our data is in accordance with the literature except the rate of extended resection procedures. This underlines the selective character of operative indications for LRRC in France as well as the care variability and the absence of optimal clinical pathway regarding these patients.